A comparative evaluation of in-vehicle side view displays layouts in critical lane changing situation. Issue 12 (2nd December 2017) - Beck, Donghyun; Lee, Minho; Park, Woojin
Abstract: This study conducted a driving simulator experiment to comparatively evaluate three in-vehicle side view displays layouts for camera monitor systems (CMS) and the traditional side view mirror arrangement. The three layouts placed two electronic side view displays near the traditional mirrors positions, on the dashboard at each side of the steering wheel and on the centre fascia with the two displays joined side-by-side, respectively. Twenty-two participants performed a time- and safety-critical driving task that required rapidly gaining situation awareness through the side view displays/mirrors and making a lane change to avoid collision. The dependent variables were eye-off-the-road time, response time, and, ratings of perceived workload, preference and perceived safety. Overall, the layout placing the side view displays on the dashboard at each side of the steering wheel was found to be the best. The results indicated that reducing eye gaze travel distance and maintaining compatibility were both important for the design of CMS displays layout. Practitioner Summary: A driving simulator study was conducted to comparatively evaluate three in-vehicle side view displays layouts for camera monitor systems (CMS) and the traditional side view mirror arrangement in critical lane changing situation. Reducing eye movement and maintaining compatibility were found to be both important for the ergonomics design of CMS displays layout.